[PP.38.07] CARDIORESPIRATORY FITNESS AND ADIPOSITY AS MORTALITY PREDICTORS IN ELDERLY. (September 2016) - de Rosa, M.; Mancini, A.; Lombardi, A.; Leosco, D.; Ferrara, N.
Abstract : Objective: Age (a) decreases physical activity (PA) increasing obesity (O) but nor associations among cardiorespiratory fitness (F), adiposity (A), nor relation between skeletal muscle mass (SMMI), body fat (BF) and all-cause mortality(M) in Elderly(E) was examined. Design and method: We performed 2 y prospective study of 77 E a 60–79 y(19.8% w) without HF, determining the association among F, A, M. F was assessed by a maximal exercise test(T), and A by body mass index (BMI), waist circumference (WC), and BF, respectively. Low F was defined as the lowest fifth of the sex-specific distribution of T duration. The distributions of BMI, WC, and percent BF were grouped for analysis according to clinical guidelines. SMMI was calculated by dividing SMMI (kg) by m2. Low SMMI was defined as the first quartile of SMMI. O (high triglycerides plus WC [HTGWC]) was defined as TG >-150 mg/dL and WC >-90 cm (m) and>-80 cm (w). The Cox proportional hazard model was used to evaluate the combined impact of O and low SMMI on cardiovascular and total M. Results: There were 8 deaths (D) during 2yr. D rates adjusted for a, sex, and examination y were across BMI groups of 18.5–24.9, 25.0–29.9, 30.0–34.9, and >- 35.0, respectively (P = .01 for trend); 13.3 and 18.2 for normal and high WC (>- 88 cm in w; >- 102 cm in m) (P = .004); 13.7 and 14.6 for normal and high percent BF (>- 30% in w; >- 25% in m) (P = .51); and 32.6, 16.6, 12.8, 12.3, and 8.1 across incremental fifths of F (P < .001 for trend). The association between WC and M persisted after further adjustment for smoking, baseline health status (S, HS), and BMI (P = .02) but not after additional adjustment for F (P = .86). F predicted M risk after further adjustment for(S;HS), and either BMI, WC, or percent BF (P < .001 for trend). Conclusions: F was a significant M predictor, independent of overall or A. To preserve functional capacity regular PA is recommended in E.